Nurses opinion of the use of Evidence-Based Nursing - Wąsowska, Iga; Kózka, Maria (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Background. Despite the many benefits arising from the use of evidence-based practice in nursing (EBN), this concept is still not systematically implemented into daily practice in Poland. Aim. The aim of the study was to investigate nurses’ opinion about the use of scientific evidence in nursing practice and the barriers for their implementation. Material and methods: The study was carried out using the method of diagnostic survey, where the instrument was an original questionnaire based on The Barriers to Research Utilization Scale (Funk, Champagne, 2010). The research was carried out in the group of 350 nurses from four hospitals in Krakow. The study was statistically analyzed. Statistical significance was assumed at the level a = 0.005 Results. The knowledge about EBN declares 30% of respondents. Among them, the largest proportion are young people (± 36 years), with higher education (93%), working in intensive care units (57%) and operating theatres (46%). The source of knowledge in the field of nursing are professional magazines (100%) and workshops in the workplace (75%). The majority of respondents did not take the activity associated with EBN. According to the respondents the main barriers in the implementation of EBN are: incomprehensibility of statistical analyzes, unclear implications for nursing practice, lack of support from the better-educated/experienced colleagues, lack of adequate salaries and also the lack of time. Conclusions. The level of nurse’s education, age and place of work have a significant influence on the level of knowledge and activities related to EBN.